Postoperative complications do not impact on recurrence and survival after curative resection of gastric cancer. Issue 1 (January 2016) - Climent, M.; Hidalgo, N.; Vidal, Ó.; Puig, S.; Iglesias, M.; Cuatrecasas, M.; Ramón, J.M.; García-Albéniz, X.; Grande, L.; Pera, M.
Abstract: Background: We assessed the impact of complications on recurrence and survival after curative gastric cancer resection. Methods: Patients undergoing R0 resections between 1990 and 2009 were identified in a prospectively maintained database and were categorized by presence of any complication Clavien-Dindo (CD) ≥ II, sepsis or intra-abdominal sepsis. Cox regression analyses to relate complications and clinico-pathological variables to time to recurrence (TTR) and overall survival (OS) were performed. Results: A total of 271 patients were included with a median follow-up of 149.9 months (range 140.1–159.9). Complications CD ≥ II occurred in 162 (59.8%) patients, sepsis in 66 (22.5%), and intra-abdominal sepsis in 37 (13.6%). Recurrence developed in 88 (32.4%) patients. Independent predictors of short TTR were pTNM stage (IIIB-IIIC vs. IA-IIA) (hazard ratio [HR] = 37.55, 95% confidence interval [CI] 17.57–80.24; p < 0.001), D1 lymphadenectomy (HR = 3.14, 95% CI 1.94–5.07; p < 0.001), and male gender (HR = 1.65, 95% CI 1.06–2.57; p = 0.026). pTNM stage (IIIB–IIIC vs. IA–IIA, HR = 10.28, 95% CI 6.51–16.23; p < 0.001), male gender (HR = 1.64, 95% CI 1.17–2.31; p = 0.005), age (HR = 1.03, 95% CI 1.02–1.05; p < 0.001), and adjuvant therapy (HR = 0.55, 95% CI 0.37–0.83; p = 0.004) were identified as independent predictors of OS.. Conclusions: Evidence provided by this study does not support a negative impact of postoperative complications CD ≥ II, sepsis, and intra-abdominal sepsis on the oncologic outcome after curative gastric cancer resection.